Título Padrão: Mudanças temporais na relação peso-comprimento de espécies de Sciaenidae (Pisces: Teleostei) no Sul do Brasil - Possamai, Bianca; Cardoso, Olímpio Rafael; Maichak de Carvalho, Barbara; Louis Spach, Henry (Arquivos de Ciências do Mar, 2021)
This study reports the importance to evaluate the length-weight relationships (LWR) across the years. We evaluate the LWR for 8 Sciaenidae species of Paranaguá Estuarine Complex, South Brazil, sampled between 2016 and 2018 by bottom trawls similar to the used by artisanal fisheries in this region. There were differences between growth type among the years for 5 species, and all species showed differences in the slope of LWR in at least one year. These results show the importance of fauna and fisheries monitoring programs to better evaluate the population dynamics and fisheries stocks. Keywords: estuarine fish, fisheries biology, marine fish, sciaenid, weight-length relationship